Challenges in Drug Discovery for Neurofibromatosis Type 1-Associated Low-Grade Glioma - Ricker, Cora A.; Pan, Yuan; Gutmann, David H.; Keller, Charles (Frontiers in Oncology, 2016)
Neurofibromatosis type 1 (NF1) is an autosomal dominant disorder that results from germline mutations of the NF1 gene, creating a predisposition to low-grade gliomas (pilocytic astrocytoma; PA) in young children. Insufficient data and resources represent major challenges to identifying the best possible drug therapies for children with this tumor. Herein, we summarize the currently-available cell lines, genetically-engineered mouse models, and therapeutic targets for these low-grade gliomas (LGGs). Conspicuously absent are human tumor-derived cell lines or patient-derived xenograft models for NF1-LGG. New collaborative initiatives between patients and their families, research groups and pharmaceutical companies are needed to create transformative resources and broaden the knowledge base relevant to identifying cooperating genetic drivers and possible drug therapeutics for this common pediatric brain tumor.